WORK LIFE BALANCE POLICIES AND THEIR IMPACT ON EMPLOYEE ENGAGEMENT & TURNOVER INTENTION: A STUDY OF EMPLOYEES IN HIGHER EDUCATION SECTOR OF RAJASTHAN - Sharma, Swati; Upadhyay, Payal Sharma (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The research explores how work-life balance policies affect faculty engagement and turnover tendencies in Rajasthan’s higher educational institutions through combined qualitative and quantitative methods. Researchers performed a structured formal survey extending over three educational institution types before conducting 20 to 30 interviews with faculty members through in-depth conversations and group sessions to obtain detailed insights about their professional experiences. Analysis using Confirmatory Factor Analysis (CFA), regression, ANOVA and t-tests shows that WLB policies decrease faculty turnover intention despite employee engagement being an inverse predictor for employee turnover. Private colleges have weaker Work-Life Balance support programs which creates increased stress and dissatisfaction levels within their faculty members. Female faculty encounter additional work-life balance difficulties because they combine caregiving tasks with inflexible workplace systems. The qualitative research established that faculty members from private institutions show dissatisfaction because of their heavy workloads and minimal availability of flexible arrangements together with limited professional advancement options. Educational institutions that provide leadership assistance together with mentoring schemes coupled with flexible rules maintain higher faculty commitment rates and boost faculty career stability. The research finds major differences between WLB policy delivery practices and actual faculty experiences that requires policy changes alongside flexible work options, gender-specific elements and defined career development tracks. Research results establish actionable guidelines which officials who lead higher education institutions and policymakers can use to strengthen faculty well-being along with ensuring institutional stability.